(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2026)
Translating idioms from English into Uzbek is one of the most demanding areas of practical translation because idioms carry meaning that is not predictable from the individual words. They are compact “packages” of culture, history, humor, and shared assumptions. When an idiom moves across languages, the translator is forced to choose between preserving meaning, preserving imagery, preserving tone, and preserving stylistic effect—and often cannot keep all four at once. Below is a focused discussion of the major challenges involved, with practical examples and strategies relevant to English→Uzbek translation.